Posterior reversible encephalopathy syndrome seen in a case of acu tepost-streptococcal glomerulonephritis: a case report - Bindu, Nagaraju Swetha; T., Neha Reddy K.; Varma, Dandu V. S. Sanjay; Hirevenkanagoudar, Usha (International Journal of Contemporary Pediatrics, 2022)
Posterior reversible encephalopathy syndrome (PRES) is a clinical and radiological condition that involves the acute onset of headache, confusion, optical impairments, and seizures with accompanying vasogenic edema on brain imaging. Here is a 12 years old male patient presented with complaints of swelling in the face and legs, headache and vomitings. He had a history of fever, sore throat and tonsillitis 12 days back. On physical examination weight and height of the patient was between 25-50th percentile, BP was 142/92 mmHg (>99th centile), he had pretibial +2 edema and periorbitol edema. At presentation urine analysis showed haematuria, proteinuria at nephritic level, elevated urea and creatinine, increased ASO titre, low C3 and C4 levels. After admission, he had an episode of convulsion when BP was 162/98 mm hg. Magnetic resonance imaging brain showed bilateral occipital, parietal, frontal cortex and subcortical white matter T2/Fluid-attenuated inversion recovery (FLAIR) hyperintensitie, suggestive of PRES. EEG was found to be normal. MRI was found to be normal in the first month after starting on antihypertensive and anticonvulsive treatment. In the first year of the follow-up, the blood pressure, neurological examination and urinalysis findings were found to be normal. Thus, it is suggested that early diagnosis of PRES in patients with clinical features and prompt treatment will prevent permanent neurologic sequale.